Globalization, Citizenship and Subjectivity: Theoritical Assumptions and Empirical Understanding in Nepalese Context - Gharti Magar, Jhakendra (Journal of Development Review, 2023)
This article attempts to show the relationship between theoretical assumptions and empirical understanding of globalization, citizenship and subjectivity. These three issues are not only interrelated each other but also controversial phenomenon in contemporary world. On the one hand, due to omnipresent nature of globalization, notions of citizenship and human subjectivity have been changing dramatically. On the other hand, citizenship derives from the existence of a community of people, a polity embedded in a geographically bounded nation state recognized by other nations and with boundaries and laws upheld, if necessary, by force. However, both globalization and citizenship are equally shaping and reconstructing the human subjectivity differently. Therefore, the main objective of the article is to explore the relationship among globalization, citizenship and subjectivity with theoretical assumptions and empirical understanding in Nepalese context. For this, in the first part of the article presents theoretical assumptions of globalization, citizenship and subjectivity followed by four Nepalese cases. More specifically, four individuals share their empirical understanding on how globalization has been shaping their human subjectivity in their own words. Finally, the article concludes that due to the globalization, human subjectivity and citizenship both also became globalizing because self and subject itself as fluid and socially constructed in globalized world.